2020
DOI: 10.1186/s10033-020-00480-0
|View full text |Cite
|
Sign up to set email alerts
|

Review and Analysis of Key Techniques in Marine Sediment Sampling

Abstract: Deep-sea sediment is extremely important in marine scientific research, such as that concerning marine geology and microbial communities. The research findings are closely related to the in-situ information of the sediment. One prerequisite for investigations of deep-sea sediment is providing sampling techniques capable of preventing distortion during recovery. As the fruit of such sampling techniques, samplers designed for obtaining sediment have become indispensable equipment, owing to their low cost, light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…30.60MPa to 28.34MPa (system-1, decreased by 7.4%) and 30.60MPa to 28.18MPa (system-2, decreased by 7.9%), respectively, which shows that the transfer device has sufficient strength and sealing performance compared with other pressure-retaining devices (Abid et al, 2015;Peoples et al, 2019;He et al, 2020). Since the volume of the system-2 chamber is greater than the volume of the system-1 chamber, the pressure drops in system-2 is greater.…”
Section: Pressure-retaining Performance Testmentioning
confidence: 90%
“…30.60MPa to 28.34MPa (system-1, decreased by 7.4%) and 30.60MPa to 28.18MPa (system-2, decreased by 7.9%), respectively, which shows that the transfer device has sufficient strength and sealing performance compared with other pressure-retaining devices (Abid et al, 2015;Peoples et al, 2019;He et al, 2020). Since the volume of the system-2 chamber is greater than the volume of the system-1 chamber, the pressure drops in system-2 is greater.…”
Section: Pressure-retaining Performance Testmentioning
confidence: 90%
“…Further, when drilling in sediment formations, the drilling fluid readily causes severe erosion on the hole wall and core. It is necessary to reasonably control the drilling fluid core surface velocity and return velocity as the bit water passage system is operated [11,12] . Core drilling uses conventional type or bottom jetting type diamond bits depending on the differences in water passage systems, as shown in Figure 2 [13][14] .…”
Section: Fig 1 Two Methods Of Seafloor Samplingmentioning
confidence: 99%
“…On the other hand, it is reported that samples from the water column do not provide a good characterization of the underlying benthic taxa suggesting that benthic biodiversity surveys should be also performed (Antich et al, 2021b;Brandt et al, 2021). Seabed sediment acquisition technologies are continuously improved and optimized, so as to obtain more authentic and reliable samples to meet the everincreasing demands on sampling capabilities (He et al, 2020) and adaptation to cabled observatory infrastructures.…”
Section: Integrating Environmental Dna With Optoacoustic Imagingmentioning
confidence: 99%